Student motivation to learn foreign languages through song in Malaysia - Husain, Salina; Jusoh, Zuraini; Mustapha, Nik Farhan; Mohd Jalis, Farhana Muslim; Ng, Boon Sim (Human Resource Management Academic Research Society, 2021)
The study was conducted to identify the effects of using song as a teaching aid for students studying foreign language at Universiti Putra Malaysia. Global language or foreign language is a compulsory course for students in Universiti Putra Malaysia. Students are required to learn this foreign language for two semesters, which is up to level two. Should they progress to level three, they will be awarded a certificate. As such, students will definitely need to have high motivation for learning the foreign language. Hence this study is undertaken to learn whether the approach is suitable to guide and enhance student’s learning capabilities. This research was conducted on 105 students who were selected at random as respondents and were given online questionnaires to complete. The questionnaire was developed based on Dörnyei's (1994) theory, which is course specific motivational components involving four constructs (interest; relevance; expectancy; satisfaction). The findings showed that students strongly agree that learning foreign language using song has the following effect: (i) it does not make them bored, (ii) the lyrics trigger their interest to learn the foreign language, (iii) the use of songs in learning helps to reinforce vocabulary, and (iv) the students feel proud when they pronounce the words correctly.